INFLUENCE OF RUPEE INSTABILITY ON INTERNATIONAL PRICING STRATEGIES OF INDIAN SMES - Harshita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The chronic fragility of the Indian rupee has become a significant concern for export-based Small and Medium Enterprises (SMEs). They are typically not very strong financially and have little access to advanced hedging instruments, which tends to limit them in trying to keep their international prices stable. The present research presumes that SMEs in the textile, engineering goods, and agro-based export industries are the most susceptible since they are the most dependent on imported inputs and vulnerable to international competition. The data is a mixture of primary and secondary information. Structured surveys of SME exporters on the topic of pricing policies, currency invoicing policy, and hedging behaviour during the past three to five years are used to collect primary data. The secondary data are based on the reports of the Reserve Bank of India, annual reviews of the Ministry of MSME, and trade statistics, and include macroeconomic indicators of rupee volatility and export performance. To analyse it empirically, a mixed-method approach is used. The quantitative analysis uses both fixed-effects panel regressions and the exchange rate pass-through models to assess the extent to which currency fluctuations influence export prices. These findings are supplemented by qualitative data on SME managers whose behavioural and strategic responses to volatility can be understood. It is projected that it will yield partial pass-through effects of rupee fluctuations into international prices, conditional on firm size, sector, and availability of hedging instruments. Those SMEs that do not possess such instruments are likely to need to be more dependent upon pricing-to-market strategies and thus some degree of compression of margins to remain competitive.